(untitled) (Fiep Bulletin - online, 2013)
This article deals with issues related to environmental education principles and concepts of sport and culture in current public policies for sport and recreation of the Ministry of Sports. The aim was to define the meaning of Environmental Education, examining concepts and actions of the sport and the city and its local processing, set changes offered by experiences of sports and cultural phenomenon, highlight contributions of the program, which the principles of Environmental Education. In general were reviewed principles and concepts of Environmental Education as a leisure time to participate and construction of sports phenomenon that offers possibilities for social change and conduct that emphasize the human nature.